(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2014)
Cancer is one of the leading causes of death worldwide. Many researchers have attempted to develop new treatments that will improve the prognosis of cancer patients. Indonesian forests, one of the most important worlds biodiversity, but little is known about chemical and/or pharmacological potential of these plants. The aim of this study to investigate selective cytotoxicity of B. virgata against of various cancer cell lines. The ethanolic extract of B. virgata leaves can act against HeLa, Widr, T47D and Vero cell lines with IC50 18.991 ± 0.234, 18.925 ± 1.277, 12.732 ± 0.945 and 16.022±0.663 ?g/ml with selective index 0.844, 0.847, 1.258 and 1.000, respectively. We highlight the significant cytotoxic effect of B. virgata from the leaves, which introduces promising expectations for new projects in chemistry, pharmacology and toxicology although non selective in these cell lines. Dhaka Univ. J. Pharm. Sci. 12(2): 123-126, 2013 (December) DOI: http://dx.doi.org/10.3329/dujps.v12i2.17615